A Framework for Improving Manufacturing Overall Equipment Effectiveness - Choi Ng, Kam; Eng Chong, Kuan (International Journal of Engineering and Technology, 2018)
Nowadays, manufacturing is getting more and more challenging and complex due to shorter product life cycle, high mixed low volume production situation, low equipment performance and volatile customer demand.  To overcome all these detractors and rising demands from all angles, manufacturer needs to be fast and agile, as efficient and as transparent as possible.  Productivity is the key factor for company in order to become competitive advantage and securing the organization work place.  Due to this strong pressure, it forces company introduce many production programs in order to fight the battle.  Production productivity programs such as Total Quality Management (TQM), Zero Defect (ZD) initiative, Next Level of Productivity (NLoP), Lean Manufacturing (LM), total productive maintenance (TPM) and Toyota Production System (TPS) are well-known to many manufacturing industries.  OEE topic has become progressively popular and widely used to improve productivity and as a research discussion in operation management.  However, OEE framework for previous studies was developed on a piecemeal basis.  This paper presents a new and complete conceptual framework that illustrates the most important factors that influence and contribute to OEE improvement.  The comprehensive framework is able to provide effective guidance and direction to industry practitioner on how to improve OEE.